Система інформаційної безпеки - Галата, Д.П.; Корнієнко, Б.Я.; Галата, Л.П. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім. Г.Є. Пухова НАН України, 2011)
The objective of an information system security is to reduce the risk of loss of confidentiality, integrity and availability of information to an acceptable level. The aim of an information system security method is to facilitate the establishment of a comprehensive, cost effective, security programme covering all key information systems. The method should assist users to establish a level of security commensurate with their requirements.